Elderly people & touchscreen device (keypad design) / Amir Syafiq Abd Aziz - Abd Aziz, Amir Syafiq Abd Aziz (2014)
In the world today, the portion of aging people grows continuously. Due to successful of healthcare services, people are living longer and the number of newborn is decreasing. This can imply that the population of young and working people is decreasing in many countries. This leads to the mean value incrementing of the mean world population's age value in the whole world. It has become more and more important to consideration human factors of elderly people in many businesses. IT product companies have to consider design of software concerning of usability for ageing people. Currently, most of the software is designed to support younger users. To support elderly users, we have to consider more on age-related differences. Since touchscreen device has totally changed the interaction experiences of an elderly users, as the touchscreen hugely popularized an elderly user become an abandon group in the rapid development of the technologies. This have been proved through the preliminary-interview "an elderly people having a problem using touchscreen device". This thesis have three objective, to find the exact problem face by the elderly, to find the suitable design feature of touchscreen device and to suggest an idea to the manufacture how the touchscreen device for an elderly people should be. The methodology used in this thesis is a qualitative research. Focus group for this project is an elderly people at the age of retirement. This project was conducted at Seksyen 7 Shah Alam, since the information could provide valuable suggestion on the further development and we hope the developer more concern about the elderly people and create more elderly user friendly touchscreen applications.